Prose Works by Alisher Navoi - qizi, Dilshoda Alisherova Azizxon (Researchparks Publishing, 2023)
The prose works of Alisher Navoi originated on the basis of prose works of different genres and different themes in Persian and Ancient Uzbek, created in Khorasan and Transoxiana. But Navoi, as a great genius, wrote such centuries, which, on the one hand, reflected a new interpretation and development of advanced prose traditions in Persian-Tajik literature. Secondly, bearing in mind the rather slow development of prose in the Uzbek language in relation to Nazm, as well as a deep understanding of the breadth of possibilities of prose in relation to Nazm, Navoi enriched Uzbek literature with about fifteen prose works.